2021
DOI: 10.1186/s43057-021-00040-9
|View full text |Cite
|
Sign up to set email alerts
|

TEVAR versus open repair of blunt traumatic descending aortic injury in polytraumatic patients involved in motor vehicle accidents

Abstract: Background Thoracic endovascular aortic repair (TEVAR) is the standard-of-care for treating traumatic aortic injury (TAI). Few retrospective studies compared TEVAR to open repair in blunt traumatic aortic injury (BTAI). Our objectives were to compare the early outcomes of TEVAR for blunt traumatic descending aortic injury to open repair (OR) in polytraumatic patients involved in motor vehicle accidents (MVA). Results Between February 2005 and April… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Similarly, the study by Cheng et al 3 showed three times higher in-hospital mortality in patients undergoing open surgical repair when compared with the endovascular repair group. Another study by Manoly et al 32 showed similar results with lower hospital mortality, blood transfusion, and postoperative infection in the TEVAR group compared with open surgery. TEVAR is currently the adopted repair technique for descending TAI due to lowered mortality, decreased paraplegia, and reduced postoperative events.…”
Section: Open Surgical Vs Endovascular Repairmentioning
confidence: 71%
“…Similarly, the study by Cheng et al 3 showed three times higher in-hospital mortality in patients undergoing open surgical repair when compared with the endovascular repair group. Another study by Manoly et al 32 showed similar results with lower hospital mortality, blood transfusion, and postoperative infection in the TEVAR group compared with open surgery. TEVAR is currently the adopted repair technique for descending TAI due to lowered mortality, decreased paraplegia, and reduced postoperative events.…”
Section: Open Surgical Vs Endovascular Repairmentioning
confidence: 71%